Cassiae semen extract ameliorates hyperlipidemia in rats by modulating lipid metabolism and FcγR-mediated immune regulation - Lv, Mingyue; Zheng, Yannan; Yuan, Man; Zhang, Errui; Zheng, Min; Liu, Guangyao; Zheng, Min; Gu, Weiliang; Xu, Hongxi (Frontiers in Pharmacology, 2025)
Introduction:Cassiae Semen Extract (CSE) shows promise in treating hyperlipidemia, although its underlying mechanisms are not yet fully understood. This study aimed to investigate the effects of CSE on hyperlipidemia in rats and explore the potential mechanisms involved.Methods:Hyperlipidemic rats were induced by a high-fat diet (HFD) and treated with CSE. Serum, liver, and fecal samples were analyzed through biochemical assays, histopathological examination, 16S rRNA sequencing, KEGG pathway analysis, and Western blot.Results:CSE treatment effectively alleviated biochemical imbalances and tissue damage induced by the HFD. 16S rRNA sequencing revealed that CSE improved gut microbiota dysbiosis and increased microbiota abundance. Pathological analysis showed that CSE reduced hepatic lipid accumulation, mitigating liver damage. KEGG pathway analysis suggested that the beneficial effects of CSE on hyperlipidemia may involve Fc gamma receptor (FcγR)-mediated phagocytosis, with immune activation influencing lipid homeostasis and liver inflammation. Western blot analysis further indicated that CSE may regulate lipid metabolism via Sterol Regulatory Element-Binding Protein-1c (SREBP-1c) and Peroxisome Proliferator-Activated Receptor Alpha (PPARα), while reducing hepatic inflammation through the MAPK signaling pathway.Discussion:CSE may ameliorate hyperlipidemia in rats by modulating gut microbiota disorders, lipid metabolism, and FcγR-mediated immune regulation, providing a potential therapeutic approach for diseases associated with metabolic dysfunction and inflammation. However, further in-depth studies are required to fully elucidate these mechanisms.